The Implementation of Cloud Technology for Collaboration and Data Management in Property Developers - Maria Veronika; Alfa Ryano Yohannis (Politeknik Pertanian Negeri Samarinda, 2025)
This study explores the impact of cloud technology implementation on collaboration, data management, and information security within a property development company. Prior to the implementation, the company faced significant challenges, including fragmented data storage, limited cross-team collaboration, and inadequate data security measures. Through a case study approach, this research analyzes the transition from a fragmented system to a centralized cloud infrastructure. The findings indicate that cloud adoption improved real-time collaboration across dispersed teams, reduced data duplication by 30%, and enhanced data security through role-based access control and encryption. Additionally, the centralized data storage system improved the accuracy of project information and sped up decision-making processes by 25%. The research also highlights how cloud technology helped the company meet compliance standards like ISO 27001 while enhancing operational efficiency. This study contributes valuable insights into how cloud solutions can streamline operations in complex industries like property development, emphasizing the need for continuous adaptation of technological solutions to meet evolving business demands.